Social Comparison on Social Media and Psychological Well-Being in Emerging Adulthood - Alda Syafira; Siti Maimunah; Iswinarti (Kirana Publisher (KNPub), 2026)
Social comparison on social media has become an increasingly prominent psychological process during emerging adulthood, driven by growing exposure to idealized portrayals of other people's lives. This study conducted a systematic review of empirical findings on the factors associated with social comparison on social media and its impact on psychological well-being during emerging adulthood. The literature search followed PRISMA guidelines across reputable academic databases, covering publications from 2022 to 2025. Of 165 articles initially identified, 18 empirical studies met the inclusion criteria. The synthesis shows that upward social comparison is the most common form of comparison and is consistently linked to lower psychological well-being, particularly through passive social media use and exposure to idealized content. Frequently identified mediating mechanisms include reduced self-esteem, impaired emotion regulation, and fear of missing out. In contrast, downward social comparison appears far less often and shows only limited protective effects. These findings highlight upward comparison as the dominant psychological risk for well-being in emerging adulthood and point to the need for interventions that strengthen social comparison awareness and emotion regulation.